1997
DOI: 10.1007/bf00946936
|View full text |Cite
|
Sign up to set email alerts
|

Topographical distribution of lactate dehydrogenase activity in human clear eye lenses and in lenses with different types of senile cataract: a histochemical investigation

Abstract: In growing clear human and bovine lenses, independent of age, the more peripherally located cortical fibers bearing cell nuclei exhibit strong enzyme-histochemical reactions. More centrally located lens areas lacking cell nuclei increase in volume in an age-dependent manner. These lens regions do not exhibit enzyme activities detectable by our histochemical technique. Therefore the lens areas free of histochemical reaction product become larger with increasing age, whereas the peripherally located lens fibers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Once the nuclei and other membrane-bound organelles are lost from the fibre cells, their ability to synthesize proteins, carry out oxidative metabolism and synthesize new membranes ceases. It has been reported that activity of lactic dehydrogenase (LDH), the last enzyme in the glycolytic pathway, ceases soon after organelle degradation [3]. If this is correct, glycolytic metabolism also ceases soon after organelle degradation, since LDH is required to produce the NAD þ required by 'upstream' steps in glycolysis.…”
Section: Lens Structure and Metabolismmentioning
confidence: 99%
“…Once the nuclei and other membrane-bound organelles are lost from the fibre cells, their ability to synthesize proteins, carry out oxidative metabolism and synthesize new membranes ceases. It has been reported that activity of lactic dehydrogenase (LDH), the last enzyme in the glycolytic pathway, ceases soon after organelle degradation [3]. If this is correct, glycolytic metabolism also ceases soon after organelle degradation, since LDH is required to produce the NAD þ required by 'upstream' steps in glycolysis.…”
Section: Lens Structure and Metabolismmentioning
confidence: 99%
“…Histochemical enzyme activities (mainly lactate dehydrogenase) in both clear lenses and cortical cataracts have only been shown to be high in lens epithelial cells and cell nuclei containing cortical lens fibers [3]. In contrast, a loss of lactate dehydrogenase activity has already been detected histochemically in all cortical fibers in the early stages of subcapsular cataracts [3].…”
Section: Biochemical and Etiological Differencesmentioning
confidence: 99%
“…In contrast, a loss of lactate dehydrogenase activity has already been detected histochemically in all cortical fibers in the early stages of subcapsular cataracts [3]. Regional distribution of adenine, guanidine and uridine (ATP, ADP, GTP and UTP) [4], and the content of glutathione [5], has been shown to be high in cortices of clear lenses and of cortical cataracts.…”
Section: Biochemical and Etiological Differencesmentioning
confidence: 99%
See 1 more Smart Citation